Evolutionarily Conserved nodE, nodO, T1SS, and Hydrogenase System in Rhizobia of Astragalus membranaceus and Caragana intermedia - Yan, Hui; Xie, Jian Bo; Ji, Zhao Jun; Yuan, Na; Tian, Chang Fu; Ji, Shou Kun; Wu, Zhong Yu; Zhong, Liang; Chen, Wen Xin; Du, Zheng Lin; Wang, En Tao; Chen, Wen Feng (Frontiers in Microbiology, 2017)
Abstract Mesorhizobium species were cardinal micro-symbionts associated with the medicinal or sand-fixation plants Astragalus membranaceus and Caragana intermedia (AC) in temperate regions of China, while all the Mesorhizobium strains isolated from each of these plants could nodulate both of them. However, Rhizobium yanglingense CCBAU01603 was a high efficiency symbiotic and competitive strain with Caragana. Therefore, the communal features that these symbiotic rhizobia shared are still remained undiscovered. In order to study the genomic background influencing the host preference of these Caragana-Astragalus symbiotic strains, the whole-genomes of 2 (M. silamurunense CCBAU01550, M. silamurunense CCBAU45272) and 5 representative strains (M. septentrionale CCBAU01583, M. amorphae CCBAU01570, M. caraganae CCBAU01502, M. temperatum CCBAU01399 and R. yanglingense CCBAU01603) that originally isolated from Astragalus membranaceus and Caragana intermedia (AC) were sequenced, respectively. As results, type III secretion systems (T3SS) of AC-rhizobia evolved in an irregular pattern, and a characteristic symbiotic and evolutionarily distinct region including nodE, nodO, T1SS and a hydrogenase system were detected in all these AC-rhizobia, moreover, nodO was verified to be prevalent distributed in other AC-rhizobia and was presumed as a factor that has an impact in the nodule formation process. In conclusion, this research interpreted the multifactorial features of the AC-rhizobia that may be associated with their host specificity at cross-nodulation group, including nodE, nodZ, T1SS as the possible main determinants; and nodO, hydrogenase system and T3SS as factors regulating the nitrogen fixation efficiency of the AC-rhizobia.